Video streaming: a case study on 3G network environment / Aziha Ab Manan - Ab Manan, Aziha (2007)
The purpose of this paper is to discuss on the performance of video streaming over 3G network. It is often difficult to determine the reason for certain behavior of streaming just by viewing the streaming server logs file. In order to study the behaviors of video streaming over 3g network, measurements of packet delay, jitter and packet loss are captured from the RTP packet analysis and a study is conducted based on the captured data. Observations method also is used to monitor the QoS of the streamed movie clip in different test cases. This paper also includes the comparison of video streaming quality with relates to different mobile environments.